2018
DOI: 10.5897/ajar2017.12708
|View full text |Cite
|
Sign up to set email alerts
|

Response of garlic (Allium sativum L.) to vermicompost and mineral N fertilizer application at Haramaya, Eastern Ethiopia

Abstract: Garlic (Allium sativum L.) is an important vegetable crop in) were recorded at the rate of 7.5 t ha -1 of vermicompost application while maximum average leaf width (1.25 cm), clove number (13.57 cm), and bulb dry matter (51.66%) were obtained at maximum rate of 130 kg ha -1 mineral N fertilizer. The results indicated that application of vermicompost at 7.5 t ha -1 and 130 kg Nha -1 mineral fertilizer gave the highest total garlic bulb yield of 12.9 and 12.69 t ha -1 , respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
2
7
1
Order By: Relevance
“…The lower harvest indices at the higher combined rates of the fertilizers could be attributed to excess vegetative growth that has a detrimental effect on partitioning of assimilates towards the bulbs. In contrary to this study, Fikru and Fikreyohannes (2018) also documented non-significant response of garlic (A. sativum L.) to vermicompost and mineral N fertilizer application for harvest index.…”
Section: Harvest Indexcontrasting
confidence: 99%
“…The lower harvest indices at the higher combined rates of the fertilizers could be attributed to excess vegetative growth that has a detrimental effect on partitioning of assimilates towards the bulbs. In contrary to this study, Fikru and Fikreyohannes (2018) also documented non-significant response of garlic (A. sativum L.) to vermicompost and mineral N fertilizer application for harvest index.…”
Section: Harvest Indexcontrasting
confidence: 99%
“…Furthermore, Verma et al (2013) reported that combined application of organic and inorganic fertilizers provided plants with all essential elements required for better plant growth and development. Also, Fikru and Fikreyohannes (2019) and obtained the similar conclusion with garlic plants. In addition, Degwale et al (2016) found that N from vermicompost as well as the inorganic N application is one of the important building blocks of amino acids (-NH 2 ), where they linked together to form proteins and make up metabolic processes required for plant growth.…”
Section: Vegetative Growth Parameterssupporting
confidence: 69%
“…In addition, vermicompost increased microbial diversity and populations, and soil fertility, as well as improved the moistureholding capacity of soils, and increased the soil cation exchange capacity (Suparno et al, 2013, Yadav andGarg 2019). Owing to vermicompost application, the highest vegetative growth, productivity and best quality were recorded as reported by Suthar (2009), Verma et al (2013), Golmohammadzadeh et al (2015, Patidar et al (2017), Acharya and Kumar (2018), Fikru and Fikreyohannes (2019), Kumar et al (2019) and Meena et al (2019) on garlic plants. Furthermore, Degwale et al (2016) found that application of 5 t ha -1 of vermicompost alone or combined with application of 46 kg N ha -1 plus 92 kg P 2 O 5 ha -1 led to the maximum vegetative growth, yield and quality of the garlic crop.…”
Section: Introductionmentioning
confidence: 59%
“…However, the lowest leaf diameter was recorded from control treatment which is without fertilizer. Similar with this result, Fikru and Fikreyohannes [23] reported that the highest leaf diameter was recorded by highest level of nitrogen fertilization 130 kg N ha −1 . The main effect of NPS fertilizer was found non-significant.…”
Section: Leaf Length and Leaf Diametersupporting
confidence: 85%
“…This result is in line with the result of Lujiu, et al [22] as verified that an increase in the level of NPK fertilizer levels increase the shoot length of garlic. Similarly Fikru and Fikreyohannes [23] reported that leaf length was significantly influenced by nitrogen fertilization. However, the main effect of nitrogen did not significantly influence this parameter.…”
Section: Leaf Length and Leaf Diametermentioning
confidence: 90%